Substance use among HIV-infected adolescents in Uganda: rates and association with potential risks and outcome factors. Issue 2 (1st February 2021) - Birungi, C.; Ssembajjwe, W.; Salisbury, T. T.; Levin, J.; Nakasujja, N.; Mpango, R. S.; Abbo, C.; Seedat, S.; Araya, R.; Musisi, S.; Gadow, K. D.; Patel, V.; et al.
ABSTRACT: This article sets out to investigate alcohol and substance use (ASU) among adolescents living with HIV (ALWH) in the sub-Saharan African setting of Uganda. A cross-sectional analysis of the records of 479 adolescents (aged between 12and 17 years) attending the study, "Mental health among HIV infected CHildren and Adolescents in KAmpala and Masaka, Uganda (the CHAKA study)" was undertaken. ASU was assessed through both youth self-report and caregiver report using the Diagnostic and Statistical Manual of Mental Disorders-5 referenced instruments, the Youth Inventory-4R and the Child and Adolescent Symptom Inventory-5 (CASI-5). Rates and association with potential risk and outcome factors were investigated using logistic regression models. The rate of ASU was 29/484 (5.9%) with the most frequently reported ASU being alcohol 22/484 (4.3%) and marijuana 10/484 (2.1%). Functional impairment secondary to ASU was reported by 10/484 (2.1%) of the youth. ASU was significantly associated with urban residence, caregiver psychological distress and the psychiatric diagnosis of post-traumatic stress disorder. On associations with negative outcomes, ASU was significantly associated with only "ever had sex". Health care for ALWH in sub-Saharan Africa should include ASU prevention and management strategies.